Perancangan Program Administrasi Pembayaran SPP, UTS dan UAS Pada MA Al-Marzukiyah Jakarta - Yamin Nuryamin; Eko Setia Budi (Universitas Budi Darma, 2020)
MA. Al-Marzukiyah is an Islamic high school parallel to senior high school. In the process of payment contributions education development, middle exam and final exam, a lot of data involved where all the data still be constructed manually. The research duty end of this is to make a design of the program payment administration based visual basic to be applied to MA. Al-Marzukiyah as a means of data processing and change manual system to a computerized system, where an instrument used to design application named ERD (Entity Relationship Diagram), LRS (Logical Relation Diagram) and Flowchart. This application made by using several software that is Microsoft Visual Basic 6.0 as software editor, Microsoft Access 2013 as a database and IcoFx 2 as symbol editor. Based program visual basic made this a strength in speed and the accuracy of in the process of data processing payment transaction, to simplify officers in data processing. This program also simplify performance in the process of reporting transaction data.